Effect of Different Non-Phytate Phosphorus Levels and Phytase Sources on Performance in Broiler Chicks - Karimi, A. (International Journal of Poultry Science, 2005)
Interest in the use of low phosphorus diets through inclusion of phytase in monogastric diets has risen due to environmental concerns. This study was carried out to investigate the effects of formulating diets varying in non-phytate phosphorus (NPP) levels and phytase sources on performance in broiler chicks. Ross® straight-run broiler chicks (n=576) were allocated to six dietary treatments, each replicated three times (32 chicks per pen) in a completely randomized design in a 3x2 factorial arrangements. Three dietary phases were employed, a starter (0-20d), grower (21-40d) and finisher (41-51d). The dietary treatments consisted of three NPP levels (0.45, 0.38, and 0.31% during starter period and 0.43, 0.36, and 0.29% during grower and finisher periods) with 500 F.T.U per kg of either sources of phytase, Natuphos® or Ronozyme P®. Measurements included body weight (BW), daily gain (DG), feed intake (FI) and feed conversion ratio (FCR). The results of this experiment showed that the chicks fed diet containing lower NPP levels had significantly lower body weight at 40 and 50d; lower daily gain during 21-40d; and higher feed conversion ratio during 21-40d period. The broiler performance was not affected by either source of phytase or the interaction between phytase source and NPP levels.